High School Private Vocational School Learning in West Kalimantan During Physical Distancing COVID-19 in 2020 - Aloysius Mering (JETL (Journal of Education, Teaching and Learning), 2021)
This study aims to reveal information about the implementation , to overcome obstacles , and the effectiveness of online learning at Senior High Schools (SMA / SMK) in West Kalimantan during Physical Distancing Covid-19 Year 202 0 . I nformation obtained s urvei purposively in nine SMA / SMK (including six elementary schools and four secondary school) in K abupaten Bengkayang, Ketapang, Hedgehog, Melawi, and Sintang West Kalimantan. Respondent teachers were 137 people.The questions that were given to respondents in detail were about the effectiveness of online learning, the media , the resources used, the obstacles faced, and the efforts to overcome these obstacles. The results of descriptive analysis of the teacher's response revealed that the "vast majority" of school (elementary, middle, high school / vocational school) has been carrying out learning online " by effectively" . Teachers plan lessons to combine online and conventional models. Also the facilities used by the teacher generally use cellphones , with the main resources being e-books, journals, videos, and question and answer materials . Learning takes advantage of the application " learning house " , " google for education " , and " own class " . The constraints general are facing is the limited "internet access" and " teacher-student-parent " who has not adaptive learning systems online. To improve e fekti v itas learning teachers make learning fun, attention to needs-style-and the student experience, as well as the evaluation of the continuous. Based on these findings, it is hoped that the government, schools, teachers, students, and parents will prioritize the provision of online learning facilities to be more successful.